Effects of resistant starch III on the serum lipid levels and gut microbiota of Kunming mice under high-fat diet - Xuhui Chen; Zhirong Wang; Di Wang; Jianquan Kan (Food Science and Human Wellness)
Resistant starch III (RS3), as a prebiotic, provides health benefits. This study aimed to investigate the role of RS3 in lowering serum lipids and regulating gut microbiota by administering Novelose 330 to Kunming (KM) mice. The results demonstrated that RS3 intervention significantly decreased body weight, food intake, levels of serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and liver fat. RS3 could remarkably improve the quality of the entire cecum, quality of the cecal wall, and wall surface area of mice; enhance the moisture content; and reduce the pH value. Moreover, the decrease in the liver TC content and the increase in the fecal TC content were related to RS3 intervention. The concentrations of total short-chain fatty acids (SCFAs) in the colon and individual levels of acetate, propionate, and butyrate increased with RS3 supplementation. An Illumina-based sequencing approach showed that RS3 notably increased the Bacteroides/Firmicutes ratio in the mice fed a high-fat diet. At the genus level, the relative abundance of Bacteroides, Ruminococcus, and Bifidobacterium and the number of main SCFA producers increased in the mice fed an RS3 diet. These findings provided insights into specific gut microbiota shifts to the hypolipidemic effect of RS3.